Analisis Pengaruh Beban Kerja, Stres Kerja dan Work Life Balance terhadap Kebahagiaan di Tempat Kerja melalui Psychological Capital (Studi pada Karyawan Level Supervisor Kontraktor Pertambangan di Kalimantan) - Imam Fikri Hadiyanto; Oetami Prasadjaningsih (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
This study examines the influence of Workload, Job Stress, and Work-Life Balance on Workplace Happiness through Psychological Capital in mining contractor supervisors in Kalimantan. Using a quantitative approach and survey method, data were collected from 132 employees through saturated sampling and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results showed that Job Stress has a positive and significant effect on Psychological Capital, while Workload and Work-Life Balance are not significant. Job Stress also has a significant negative impact on Happiness at Work, while Workload and Work-Life Balance have no significant effect. Psychological Capital has a positive and significant influence on Happiness at Work. In the mediation analysis, only Work Stress has a significant effect on Happiness at Work through Psychological Capital. These findings highlight the importance of managing Job Stress, developing Psychological Capital, and innovative strategies to improve Work-Life Balance in the mining industry. The practical implications include more proactive stress management policies as well as a holistic approach in improving employee well-being.